Communication with Chronic Patients Weaning from Mechanical Ventilation: A Qualitative Study on Iranian ICU Caregivers - Ali Khalafi; Sara Adarvishi; Farhad Soltani (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Mechanical ventilation in chronic patients is associated with major risks and complications. Therefore, rapid and safe weaning from mechanical ventilation is of great importance. Objectives: The present study aimed to explain the communication strategies with chronic patients weaning from mechanical ventilation from the perspective of the intensive care unit (ICU) staff. Methods: In this descriptive qualitative study, the participants included 12 ICU nurses, three nurse managers, and three patients, who were selected via purposive and maximum variation sampling from hospitals of Ahvaz in southwest of Iran. To collect the data, the researcher conducted semi-structured interviews using open questions. The recorded interviews were then transcribed and analyzed via conventional content analysis in MAXQDA. Results: The two main themes identified in this study were [1] the time spent with the patient and [2] the soothing umbrella that indicated the importance of communication with the patients during the weaning process and the significance of nurses' use of communication strategies. Conclusion: Communication strategies can lead to a better understanding of the patients and management of the weaning process. On the other hand, loss of communication skills can hinder the process of weaning. Therefore, improved communication skills and active bedside presence are recommended.